Adalimumab for Sintilimab-Induced Toxic Epidermal Necrolysis in a Patient with Metastatic Gastric Malignancy: A Case Report and Literature Review - Zhang L; Wu Z (Dove Medical Press, 2023)
Li Zhang, Zhongxiao Wu Department of Dermatology, Ningbo No 6 Hospital, Ningbo, 315040, People's Republic of ChinaCorrespondence: Zhongxiao Wu, Email wzx2033@163.comAbstract: Sintilimab is a recombinant fully human anti-programmed cell death protein 1 (PD-1) monoclonal antibody that blocks the interaction of PD-1 with its ligand. It was approved to use in patients with gastric malignancy. Toxic epidermal necrolysis (TEN) is a rare, life-threatening cutaneous drug reaction. Here, we report a 70-year-old female patient with gastric malignancy who developed severe TEN 10 days after initiation of sintilimab. The patient did not respond to the systemic corticosteroids and intravenous immunoglobulin therapies but improved after the subcutaneous injection of adalimumab (40 mg) that is a monoclonal antibody directed against antitumor necrosis factor-α. Her rashes rapidly resolved within 24 hr. By the seventh day, the bullae had scabbed and most skin lesions had subsided. The patient showed no sign of organ dysfunction. This is the first reported case of immune checkpoint inhibitor-induced TEN successfully treated with adalimumab.Keywords: adverse events, gastric malignancy, sintilimab, programmed death-1 inhibitor, toxic epidermal necrolysis, antitumor necrosis factor-&#x03B1